2014
DOI: 10.1007/s13762-014-0701-1
|View full text |Cite
|
Sign up to set email alerts
|

Manganese dioxide nanoparticles-silver-Y zeolite as a nanocomposite catalyst for the decontamination reactions of O, S-diethyl methyl phosphonothiolate

Abstract: The decontamination reactions of O,S-diethyl methyl phosphonothiolate, as an agricultural organophosphorous pesticide onto 20 wt% loaded manganese dioxide nanoparticles-silver-Y zeolite as a nanocomposite catalyst in different solvents, were evaluated and monitored by means of gas chromatography-flame ionization detector and gas chromatography-mass spectrometry. Prior to the reaction, the catalyst was synthesized in three steps: at first, sodium-Y zeolite was prepared by hydrothermal method; then, silver-Y zeo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…K. Dastafkan et al [102] (2015) reported 20 wt% MnO 2 NPs-AgY zeolite catalysts in different solvents for decontamination reactions of O,S-diethyl methyl phosphonothiolate (OSDEMP), as an agricultural organophosphorus pesti-International Journal of Nonferrous Metallurgy cide. This reaction was studied by GC-FID and GC-MS techniques.…”
Section: Literature Surveymentioning
confidence: 99%
“…K. Dastafkan et al [102] (2015) reported 20 wt% MnO 2 NPs-AgY zeolite catalysts in different solvents for decontamination reactions of O,S-diethyl methyl phosphonothiolate (OSDEMP), as an agricultural organophosphorus pesti-International Journal of Nonferrous Metallurgy cide. This reaction was studied by GC-FID and GC-MS techniques.…”
Section: Literature Surveymentioning
confidence: 99%
“…The Elovich equation can be simplified if it is presumed that abt ) 1. At the boundary conditions qt ¼ 0 at t ¼ 0, the above mentioned equation changes to (18) [45]. Plot of Elovich kinetics is given.…”
Section: Elovich Kinetic Modelmentioning
confidence: 99%
“…As reported in previous researches, the natural clinoptilolite zeolite shows a high adsorbent capacity for the removal of non-radioactive strontium ions [16,17]. The procedures for modifying zeolites are usually done by impregnation [18] and ion-exchange [17]. Also, the dispersion of metal oxide nanoparticles onto zeolite depends on the type of metal precursor used and its action during the preparation method.…”
Section: Introductionmentioning
confidence: 99%
“…The surface atoms are unsaturated and have high chemical activity and adsorption capacity to many substances [9]. High surface area and the reactive sites tailored in the form of edge and corner defects along with unusual lattice planes react in a stoichiometric way, thereby rendering the adsorbed toxic agents into non-toxic and less-toxic ones [10]. Besides, the reactions are analogous to their solution behavior.…”
Section: Introductionmentioning
confidence: 99%